Analysis of Potential Development of Goat Farming at Bantul Regency, in Special Region of Yogyakarta, Indonesia - Nirmala, Regita Aisyah; Atmoko, Bayu Andri; Andarwati, Siti; Panjono, Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The objective of study was to analyze the potential development of goat farming at Bantul Regency, in Special Region of Yogyakarta, Indonesia. The research was conducted from January to April 2023. Data collection were obtained from stakeholder i.e farmers, goat traders, the Central Statistics Agency, the Food Security and Agriculture Office, the Communication and Information Office. These data were collected by using interview, survey, and direct observation. The collected data then were analyzed to calculate; population dynamics, location quotient, growth share, population pressure, carrying capacity and carrying capacity index (CCI). Analysis of the location quotient were five sub-districts which included in the base sector. Analysis of the growth share were Bantul Regency included in the leading sectors. Bantul Regency has not been experienced population pressure. The potential for feed dry matter at Bantul Regency was 82.319,68 tons dry matter/year. There was potential for the development of goats around 17.186,77 animal unit. To a large extent, the Bantul Regency area was obtained CCI values above 2 which was safe criteria. In conclusion, Bantul Regency has good potential in the development of goat. Then, the potential needs support from the government, private sector and the community.